Idiopathic calcified myocardial mass. Issue 5 (September 1974) - Patterson, David; Gibson, Derek; Gomes, Ricardo; McDonald, Lawson; Olsen, Eckhardt; Parker, John; Ross, Donald
Abstract : Patterson, D., Gibson, D., Gomes, R., McDonald, L., Olsen, E., Parker, J., and Ross, D. (1974). Thorax, 29, 589-594. Idiopathic calcified myocardial mass. Myocardial calcification can be subdivided into three groups—metastatic, dystrophic or an extension inwards from the pericardium. This case in which the calcified myocardial mass was initially delineated by radiography and by echocardiography and subsequently removed does not fit into any subdivision and has been termed idiopathic.